2015
DOI: 10.1155/2015/747693
|View full text |Cite
|
Sign up to set email alerts
|

RhoGTPases as Key Players in Mammalian Cell Adaptation to Microgravity

Abstract: A growing number of studies are revealing that cells reorganize their cytoskeleton when exposed to conditions of microgravity. Most, if not all, of the structural changes observed on flown cells can be explained by modulation of RhoGTPases, which are mechanosensitive switches responsible for cytoskeletal dynamics control. This review identifies general principles defining cell sensitivity to gravitational stresses. We discuss what is known about changes in cell shape, nucleus, and focal adhesions and try to es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 149 publications
1
28
0
4
Order By: Relevance
“…Rho, Cdc42 and Rac are recognized as the most important regulators of actin assembly (Lee and Dominguez 2010). During SMG, the reorganization of actin cytoskeleton may be attributed to Rho, which is reported to act as a sensor for microgravity (Louis et al 2015). To clarify the mechanism of SMG remodeling F-actin, we utilized Y-27632, an inhibitor of Rock (a downstream factor of Rho), and found that Y-27632 significantly reversed the reorganization of F-actin induced by SMG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rho, Cdc42 and Rac are recognized as the most important regulators of actin assembly (Lee and Dominguez 2010). During SMG, the reorganization of actin cytoskeleton may be attributed to Rho, which is reported to act as a sensor for microgravity (Louis et al 2015). To clarify the mechanism of SMG remodeling F-actin, we utilized Y-27632, an inhibitor of Rock (a downstream factor of Rho), and found that Y-27632 significantly reversed the reorganization of F-actin induced by SMG.…”
Section: Discussionmentioning
confidence: 99%
“…Rock phosphorylates LIM kinase, which then phosphorylates confilin, resulting in actin cytoskeleton stabilization (Nakashima and Lazo 2010). It has been reported that Rho-GTPases act as key sensors in cell adaptation to microgravity and mediates the reorganization of actin cytoskeleton under microgravity (Louis et al 2015). But the role of Rho signaling in cell migration under microgravity is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, they seem to be at the forefront in cell adaptation to microgravity. According to Louis et al (186), on 1 ×  g , cell tension is sensed through the cytoskeleton via microtubules, intermediate filaments, and actin stress fibers associated with focal adhesions within the extracellular matrix. These elements are controlled by GTPases RhoA and Rac1.…”
Section: Cytoskeletonmentioning
confidence: 99%
“…The previously described rapid reaction and adaptation of an oxidative burst reaction [ 32 ] suggests a direct effect on the NADPH oxidase, which is a membrane-bound multiprotein complex closely associated with cytoskeletal dynamics [ 58 , 59 ] and mechanosensitivity [ 3 ]. Also, RhoGTPases are potential candidates to explain the structural cellular changes in microgravity [ 60 ]. In our study, we detected a significant up-regulation of p22 phox after 20 s and of p47 phox after 5 min of microgravity, whereas rac-1 was down-regulated after 5 min of microgravity.…”
Section: Discussionmentioning
confidence: 99%